THE PERSONAL LIBRARY OF PRESIDENT ANTANAS SMETONA: RESEARCH AND HERITAGE - LIETUVNINKAITĖ, NIJOLĖ (Knygotyra, 2011)
The article aims to describe the personal library heritage of the first President of Lithuania Antanas Smetona (1874–1944), its storage and research issues. Through the study of authentic sources and methods of book science, the author managed to reveal and summarize the fate of the personal library and the structure, diffusion and the current state of the heritage, but a more detailed investigation should be extended. In 1941, A. Smetona withdrew from Lithuania. The Kaunas University Library got 913 copies of publications from his personal library. In Soviet times it was dispersed to several offices, and some publications were destroyed, but more than half of the library heritage survived. Currently, most (560) publications are stored in the Kaunas University of Technology Library and other 209 in the Library of Vilnius University, Kaunas County Public Library and other institutions. The survey data suggest that the President’s personal library was dominated by the humanities and social sciences. Most publications were in German and French. The library had rare sixteenth–eighteenth century prints in Lithuanian. There are artistic bookbindings with A. Smetona’s super-ex-libris and various inscriptions. The conclusion it that the president purposefully collected a personal library that corresponded to his political and social, scientific and personal interests. Its memorial value as of the personal library of the first President of Lithuania allows considering this heritage as endangered and desiring a scientific reconstruction.